Towards understanding the enhancement of moisture diffusion during intermediate-infrared drying of peach pomace based on the glass transition theory. (June 2019) - Zhou, Mo; Li, Cong; Bi, Jinfeng; Jin, Xin; Lyu, Jian; Li, Xuan
Abstract: The aim of this study is to understand the moisture diffusion during intermediate-wave infrared radiation (IWIR) based on glass transition theory. Peach pomace was subjected by IWIR and hot air (HA) drying at 60, 70 and 80 °C. Compared to HA drying, IWIR showed high dehydration performance characterized by shorter drying time, higher drying speed and higher effective moisture diffusivity ( D eff ). The variations of sample temperature and D eff were presented in different patterns between HA and IWIR. The state diagram of peach pomace showed higher ΔT ( T – T g ) of IWIR compared to HA in all conditions. A significant increase of Δ T value was observed during the mid-stage of IWIR process. These results demonstrated that IWIR is an effective method for pomace drying, which can keep high drying rate and a uniform dehydration process during the whole process by overcoming the diffusion-inhibitory effect. Industrial relevance This paper investigated the drying behavior and water diffusion between intermediate-infrared drying and hot air drying on peach pomace. The results revealed that compared to hot air drying, which is commonly used in industrial drying of pomace, intermediate-infrared drying is a more effective drying method for pomace characterized by shorter drying time, higher drying speed and higher effective moisture diffusivity. It can keep relative high drying rate during the whole dehydration process via overcoming the diffusion-inhibitory effect caused by case-hardening phenomenon. The results of this study suggested that intermediate-infrared radiation would be an effective method in industrial drying of fruit pomace alternative to hot air drying. Highlights: IWIR showed higher dehydration performance than HA on peach pomace drying. IWIR and HA presented different patterns in heating curve and D eff variation. A significant increase of T – T g value was observed in the mid-stage of IWIR.